(untitled) (E Conference Zone, 2022)
Protest speech rejection, objection, discussion, all negatives such as prohibition, disapproval combines reactions. In the same way. The act of protesting together is complex and multifaceted aspect phenomenon, semantic, grammatical and taking into account pragmatic aspects should be investigated.